Genu valgum in children. Issue 6 (December 2022) - Buchan, Stephanie; Bennet, Simon; Barry, Matthew
Abstract: Genu valgum is a common lower limb deformity seen in children. There are multiple causes for the development of genu valgum but to be able to accurately assess the child it is important to understand the physiological development of the lower limbs. Although often asymptomatic and idiopathic, genu valgum can be associated with underlying pathology, such as rickets, previous proximal tibia fracture leading to valgus deformity, tumours and dysplasias which often require a multidisciplinary approach to management of the condition. This article will review the common causes of genu valgum in children, explain how to clinically assess the child and cover possible management options for each condition.